Authorea
DOI: 10.22541/au.158456420.05413475
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal-associated invariant T (MAIT) cells are activated in the gastrointestinal tissue of patients with combination ipilimumab and nivolumab therapy-related colitis in a pathology distinct from ulcerative colitis.

Abstract: The aim of this study was to investigate the pathogenesis of combination ipilimumab and nivolumab-associated colitis (IN-COL) by measuring gut-derived and peripheral blood mononuclear cell (GMNC; PBMC) profiles. We studied GMNC and PBMC from patients with IN-COL, IN-treated with no adverse-events (IN-NAE), ulcerative colitis (UC) and healthy volunteers by flow cytometry. In the gastrointestinal-derived cells we found high levels of activated CD8+ T cells and mucosal-associated invariant T (MAIT) cells in IN-CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We previously demonstrated that the majority of T cells in the colon of ICI-colitis were CD8 þ . 10 We sought to determine whether these CD8 þ T cells had a T RM cell phenotype. We found that both UC and DCC groups are associated with increased proportions of CD3 þ T cells in the affected tissue compared with healthy gut and DCNC groups, respectively (Figure 2Ai).…”
Section: Memory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the majority of T cells in the colon of ICI-colitis were CD8 þ . 10 We sought to determine whether these CD8 þ T cells had a T RM cell phenotype. We found that both UC and DCC groups are associated with increased proportions of CD3 þ T cells in the affected tissue compared with healthy gut and DCNC groups, respectively (Figure 2Ai).…”
Section: Memory T Cellsmentioning
confidence: 99%
“…The available data suggested that anti-CTLA-4-associated colitis is associated with CD8 þ T cells 8 and an up-regulation of Th1 and Th17 effector pathways, including interferongamma (IFNG). 9 We previously demonstrated that anti-CTLA-4/PD-1 colitis is associated with high levels of activated (HLA-DR þ CD38 þ ) memory CD8 þ T cells, 10 and lower proportions of regulatory T cells compared with UC. 10 We hypothesized that CD8 þ T RM cells are implicated in the pathogenesis of ICI-colitis, postulating that they would become activated in an off-target consequence, and sought to understand the signaling pathways involved (Figure 1).…”
mentioning
confidence: 99%
“…At the protein level, these exhaustion markers were significantly upregulated in the 5-OP-RU condition, suggesting that chronic antigen-specific activation strongly induces negative feedback mechanisms to suppress further activation and proliferation. Taken together, these data imply that checkpoint blockade may enhance MAIT cell activity against infectious or malignant disease (Boulouis et al, 2020;Leeansyah et al, 2015;Venken et al, 2018) or contribute to autoimmune complications of immunotherapy (Sasson et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The copyright holder for this preprint this version posted October 24, 2020. ; https://doi.org/10.1101/2020.10.22.351262 doi: bioRxiv preprint Leeansyah et al, 2015;Venken et al, 2018) or contribute to autoimmune complications of immunotherapy (Sasson et al, 2020).…”
mentioning
confidence: 99%
“…These indices include the MES, 17,27,[30][31][32][33] the van der Heide Score, 27,34 the Ulcerative Colitis Endoscopic Index of Severity (UCEIS), 31,35,36 and the Simple Endoscopic Score for Crohn's Disease (SES-CD). 35 Notably, several of the endoscopic features identified in this review are component items of IBD indices.…”
Section: Assessment Of Endoscopic Disease Activity In Icicmentioning
confidence: 99%